Community Empowerment to Optimize Stunting Prevention Through Processed Local Fish in Teluk Rhu: Pemberdayaan Masyarakat Guna Optimalisasi Pencegahan Stunting Melalui Olahan Ikan Lokal Teluk Rhu - agrina, agrina; Dewita; Sri Endang Kornita; Yuliana, Serly Sigi; Trianti, Rana Roidah (Universitas Lancang Kuning, 2025)
Stunting is still a nutritional problem in infants and toddlers nationally. The purpose of the service is to improve the ability of the community, especially the UPKKA Maju Bersama partner group in utilizing local fish as a source of animal protein in Teluk Rhu Rupat Utara village. Service activities are carried out through socialization methods, training in processing local fish products (parang fish), mentoring and monitoring evaluation. The results of the service showed that the ability of the UPKKA group increased in the aspect of diversifying 4 processed local fish products (dragon feet, risoles, chocolate cookies and noodles). There was an increase in average knowledge from 7.3 to 9.3, nutritional attitudes and behaviors from 41.8 to 44.5 and 44.6 in 12 families with stunted toddlers. The conclusion of this activity is that it needs follow-up from the local government so that this activity continues because in addition to being able to overcome nutritional problems (stunting) it can also open up opportunities for economic improvement for the community because Teluk Rhu village is a tourist area so that its economic value is quite high